Hawking-like radiation of charged particles via tunneling across the lightcylinder of a rotating magnetosphere - Huiquan Li (Elsevier, 2022)
In rotating magnetospheres planted on compact objects, there usually exist lightcylinders (LC), beyond which the rotation speed of the magnetic field lines exceeds the speed of light. The LC is a close analog to the horizon in gravity, and is a casual boundary for charged particles that are restricted to move along the magnetic field lines. In this work, it is proposed that there should be Hawking-like radiation of charged particles from the LC of a rotating magnetosphere from the point of view of tunneling by using the field sheet metric.